Ho Chi Minh City (Saigon) - Florence, Mason (Lonely Planet, 2001)
Contains an essential historical and cultural guide to major attractions and out-of-the-way sights; detailed accommodation for every budget; the best in Saigon cuisine; fascinating excursions to the Mekong Delta and seaside retreats; and an indispensable Vietnamese language chapter.